PENGARUH INFLASI DAN PROFITABILITAS TERHADAP HARGA PASAR SAHAM - Firdiana, Merindha; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of the research is to find out and to analyze the influence of inflation and profitability to the stock market price of manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2014 periods. The sample collection has been carried out by using purposive sampling method, and the samples are 73 companies manufacturing with the observation period from 2012 to 2014, so 219 observation data have been obtained. The secondary data sources in this research have been obtained from the official website of Indonesia Stock Exchange. The data analysis technique has been done by using multiple linear regressions analysis and SPSS program. Based on the result of the analysis, it can be concluded that (1) Inflation has significant and negative influence to the stock market price on the companies which are listed in the Indonesia Stock Exchange. (2) Profitability (ROA) has significant and positive influence to the stock market price of the manufacturing companies which are listed in Indonesia Stock Exchange.Keywords: Inflation, profitability, stock price